2020
DOI: 10.1021/acsami.0c09046
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Moisture-Resistive Perovskite Films for Highly Efficient Solar Cells Using Molecule Incorporation

Abstract: The development of high-crystalline perovskite films with large crystal grains and few surfacedefects is attractive to obtain high performance perovskite solar cells (PSCs) with good device stability. Herein, we simultaneously improve the power conversion efficiency (PCE) and humid stability of the CH 3 NH 3 PbI 3 (CH 3 NH 3 =MA) device by incorporating small organic molecule IT-4F to the perovskite film and using buffer layer of PFN-Br. The presence of IT-4F in the perovskite film can successfully improve cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Amazingly, even under extreme conditions (a drop of water was dripped onto the perovskite films coated with ETL), PCBB–S-N/PCBM-coated perovskite film shows strong moisture resistance, which can survive more than 240 s. In stark contrast, the color of the PCBM-coated perovskite films immediately changed from black to yellow. Moreover, studies have shown that adding IT-4F to the perovskite film can improve crystallinity and increase the grain size, thereby reducing trap states, extending the charge carrier lifetime, and making the perovskite film hydrophobic . After storage for 30 d in an environment with 10–30% relative humidity, the unencapsulated device based on the IT-4F modified perovskite film retains ∼80% of the initial PCE (20.55%).…”
Section: Improving the Humidity Stability Of Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amazingly, even under extreme conditions (a drop of water was dripped onto the perovskite films coated with ETL), PCBB–S-N/PCBM-coated perovskite film shows strong moisture resistance, which can survive more than 240 s. In stark contrast, the color of the PCBM-coated perovskite films immediately changed from black to yellow. Moreover, studies have shown that adding IT-4F to the perovskite film can improve crystallinity and increase the grain size, thereby reducing trap states, extending the charge carrier lifetime, and making the perovskite film hydrophobic . After storage for 30 d in an environment with 10–30% relative humidity, the unencapsulated device based on the IT-4F modified perovskite film retains ∼80% of the initial PCE (20.55%).…”
Section: Improving the Humidity Stability Of Pscsmentioning
confidence: 99%
“…Moreover, studies have shown that adding IT-4F to the perovskite film can improve crystallinity and increase the grain size, thereby reducing trap states, extending the charge carrier lifetime, and making the perovskite film hydrophobic. 122 After storage for 30 d in an environment with 10−30% relative humidity, the unencapsulated device based on the IT-4F modified perovskite film retains ∼80% of the initial PCE (20.55%). 3.4.…”
Section: Improving the Humidity Stability Of Pscsmentioning
confidence: 99%
“…Cationic poly[9,9dioctyl-9′,9′-bis[3-(ethyl(dimethyl)ammonio)propyl][2,2′-bi-9Hfluorene]-7,7′-diyl bromide, namely PFN-Br, was chosen as the energy donor due to its strong light harvesting ability, excellent photoelectric properties and promising photocatalytic activity. [27,28] However, PFN-Br shown strong fluorescence in CH 3 OH with photoluminescence quantum yield (PLQY) up to 0.53 (coumarin 153 in ethanol as the fluorescence reference). Clearly, this large energy loss though fluorescence irradiation is not beneficial to photochemical conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous efforts have been made to overcome these obstacles, for instance, by incorporating small molecules [26], using an efficient electron transport layer [27], blending of acceptor and donor materials [28], and integrating conventional semiconductors such as metal oxides and functional 2D materials [14,19]. For instance, Chen et al proposed the multilayer structure of organic/inorganic materials for attaining high responsivity in hybrid photodetectors [29].…”
Section: Introductionmentioning
confidence: 99%